Representation of Spatial and Feature Information in the Monkey Dorsal and Ventral Prefrontal Cortex - Constantinidis, Christos; Qi, Xue-Lian (Frontiers in Integrative Neuroscience, 2018)
The primate prefrontal cortex is critical for executive functions including working memory, task switching, and response selection. The functional organization of this area has been a matter of debate over a period of decades. Early models proposed segregation of spatial and object information represented in working memory in the dorsal and ventral prefrontal cortex, respectively. Other models emphasized the integrative ability of the entire prefrontal cortex depending on task demands, not necessarily tied to working memory. An anterior-posterior hierarchy of specialization has also been speculated, in which progressively more abstract information is represented more anteriorly. Here we revisit this debate, updating these arguments in light of recent evidence in non-human primate neurophysiology studies. We show that spatial selectivity is predominantly represented in the posterior aspect of the dorsal prefrontal cortex, regardless of training history and task performed. Objects of different features excite both dorsal and ventral prefrontal neurons, however neurons highly specialized for feature information are located predominantly in the posterior aspect of the ventral prefrontal cortex. In accordance with neuronal selectivity, spatial working memory is selectively impaired by inactivation or lesion of the dorsal prefrontal cortex and object working memory by ventral inactivation or lesion. Neuronal responses are plastic depending on task training, but training too has dissociable effects on ventral and dorsal prefrontal cortex, with the latter being more plastic. Despite the absence of an overall topography, evidence exists for the orderly localization of stimulus information at a sub-millimeter scale, within the dimensions of a cortical column. Unresolved questions remain, regarding the existence or not of a functional map at the areal and columnar scale, and the link between behavior and neuronal activity for different prefrontal subdivisions.